Maximal fat oxidation: comparison between treadmill, elliptical and rowing exercises - Filipovic, M.; Munten, S.; Herzig, K. H.; Gagnon, D. D. (Journal of Sports Science & Medicine, 2021)
Fat oxidation during exercise is associated with cardio-metabolic benefits, but the extent of which whole-body exercise modality elicits the greatest fat oxidation remains unclear. We investigated the effects of treadmill, elliptical and rowing exercise on fat oxidation in healthy individuals. Nine healthy males participated in three, peak oxygen consumption tests, on a treadmill, elliptical and rowing ergometer. Indirect calorimetry was used to assess maximal oxygen consumption (VO2peak), maximal fat oxidation (MFO) rates, and the exercise intensity MFO occurred (Fatmax). Mixed venous blood was collected to assess lactate and blood gases concentrations. While VO2peak was similar between exercise modalities, MFO rates were higher on the treadmill (mean ± SD; 0.61 ± 0.06 g·min-1) compared to both the elliptical (0.41 ± 0.08 g·min-1, p = 0.022) and the rower (0.40 ± 0.08 g·min-1, p = 0.017). Fatmax values were also significantly higher on the treadmill (56.0 ± 6.2 %VO2peak) compared to both the elliptical (36.8 ± 5.4 %VO2peak, p = 0.049) and rower (31.6 ± 5.0 %VO2peak, p = 0.021). Post-exercise blood lactate concentrations were also significantly lower following treadmill exercise (p = 0.021). Exercising on a treadmill maximizes fat oxidation to a greater extent than elliptical and rowing exercises, and remains an important exercise modality to improve fat oxidation, and consequently, cardio-metabolic health.